A Christian field guide to technology for engineers and designers - Brue, Ethan J., 1968-; Schuurman, Derek (Derek C.); VanderLeest, Steven H., 1966- (Downers Grove IVP Academic, 2022)
"Technology and its power are both old and new-as is the wisdom needed to envision, design, and use it well. In this field guide for Christians studying and working in technology, case studies, historical examples, and personal stories encourage readers to ask harder questions, aspire to more noble purposes, and live a life consistent with their faith as they engage with technology"--
Includes bibliographical references (pages 209-218) and index.
Keywords: Technology -- Religious aspects; Religion and science; Engineering -- Vocational guidance; Design -- Vocational guidance